PENERAPAN MODEL PEMBELAJARAN PREDICT-OBSERVE-EXPLAIN UNTUK MENINGKATKAN HASIL BELAJAR KOGNITIF SISWA PADA MATERI MOMENTUM DAN IMPULS DI KELAS X MIA SMAN 1 KAMPAR TIMUR - Rahayu Fitri; Zulhelmi Zulhelmi; Muhammad Nasir (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This study aims to describe of cognitive learning competense and to know the increasing in students' cognitive learning through the application of the Predict-Observe Explain learning model and conventional learning in momentum and impuls material. The research method used is quasy experiment with the design of Control Group Design Pretest-Posttest. The population is all students of class X MIA SMAN 1 Kampar Timur. Samples of two classes were selected by random sampling, obtained by class X MIA 4 consist to 37 people as the experimental class and class X MIA 3 consist to 37 people as the control class. Data have colecte use cognitive test instrument. Data were analyzed descriptively by looking at the results of differences in the increase in cognitive learning outcomes of the experimental and control class students then analyzed inferentially by using the T-test. The results showed that there were differences in the increase in students' cognitive learning outcomes in momentum and impulse material in class X MIA SMAN 1 Kampar Timur. The average cognitive learning outcomes of the experimental class students were higher than the control class. Based on the results of this study it can be concluded that the Predict-Observe-Explain learning model can improve cognitive learning outcomes in the material momentum and impulses of class X MIA SMAN 1 Kampar Timur.Key Words: Cognitive Learning Outcomes, Predict-Observe-Explain, Momentum andImpulses